Impact of a normal or non-specific admission ECG on the treatment and early outcome of patients with myocardial infarction in Swiss hospitals between 2003 and 2008 (Swiss Medical Weekly, 2010)
Background: Diagnosis of acute myocardial infarction (AMI) rests upon clinical, electrocardiographic and biochemical parameters. Previous studies reported AMI patients who present with non-specific ECGs. Objectives: To examine clinical or demographic features of AMI patients presenting with or without ECG changes and assess the impact of these ECGs on treatment and outcome. Methods: Using the AMIS Plus data, patients admitted between 2003 and 2008 with a definite diagnosis of AMI (clinical symptoms, elevated troponin levels) were stratified according to the admission ECG into group 1 with normal/non-specific ECGs and group 2 with ECG changes. Results: Of 14 957 patients, 1085 (7.3%) belonged to group 1 and 13 872 (92.7%) to group 2. There were no differences between the two groups in age (65.9 yr vs. 65.4 yr), gender (28% female), diabetes (19% vs. 18%), hypertension (61% vs. 59%), family history (35% vs. 33%) or smoking (37% vs. 38%). Dyslipidaemia (62% vs. 56%; p 30 kg/m2 [23% vs. 19%; p = 0.003]) were more frequent in group 1 who were admitted longer after symptom onset (280 min vs. 230 min). Patients in group 1 were exposed to less intensive pharmacological and interventional treatments (aspirin [93.6% vs. 95.3%; p = 0.012], clopidogrel [70% vs. 73%; p = 0.046], unfractionated heparin [59% vs. 65%; p